Acción de trichoderma sp. en el control de patógenos del suelo en el cultivar pimiento, Machala - Centeno Alvear, Elvis Isaac (2011)
The investigation work of Trichoderma sp. between the months of January to March 2011 in the Faculty of Agriculture Sciences of The Machala University Technical. It is located to 5.5 km of the Machala, El Cambio parish, Machala canton, El Oro Province, Ecuador country.The outlined objectives were. 1. Determinate the Trichoderma action against of the pathogen on the ground at the beginning and the post production of pepper in Machala canton. 2. Determinate which of the used methods are more efficient and. 3. An economic study has to be carried out about the treatment.The treatments were about the application of the before antagonist (T1), simultaneous (T2), y after of the pathogen (T3), a chemical witness (T4), that is previously inoculated the pathogen and a witness absolute (T5); rather the antagonist and the pathogen were produced in stock mother in a crop PDA (Dextrosa Patata Agar), and its massive production in a pre-cooked rice.The designs used to study the effect of the Trichoderma were blocks at random with 5 treatments and 4 repetitions. The variables studied were: The number of the affected plants; the high of the plant, root length, root weight, time production, number of the fruits per plant, fruit weigh, fruit length, fruit diameter and the output per treatments. The studies of variety and the Duncan test with a 5% of the significant level determinate a high statistic significant between the treatments. In all the studied variables the treatment of the before application was superior in statistic to the absolute witness; chemical witness and the transplant and the sowing. With a difference higher in the relation between the benefits and the cost of 2,04 for the before application and 0,08 for the chemical witness; meanwhile for the absolute witness and after application it doesn’t cover the investment charges.It’s important that the best phase of application for getting more control of the pathogens is at the moment of the transplant; because it work as a root protector; because the pepper plant during the first month are more vulnerable in the attack of the pathogens; also it is a help improving the ground quality and the contamination rates are controlled where the sowing is carried out.